Prognosis of patients receiving induction chemotherapy for locally advanced or lymph node metastatic bladder cancer. (November 2020) - Le Goux, Constance; Neuzillet, Yann; Rouanne, Mathieu; Gachet, Julie; Staub, Fabrice; Hervé, Jean-Marie; Yonneau, Laurent; Abdou, Ali; Ghoneim, Tarek; Théodore, Christine; Lebret, Thierry
Background: Induction chemotherapy is recommended before surgery for unresectable muscle-invasive bladder cancer, locally advanced or lymph node disseminated disease. These patients' prognoses cannot be extrapolated from data regarding neoadjuvant chemotherapy, which is performed in operable patients. Objective: We assessed the prognosis of patients undergoing induction chemotherapy for locally advanced or lymph node metastatic bladder cancer. Methods: We analysed patients with cT4NxM0 or cTxN+M0 bladder cancer treated by induction chemotherapy between 2006 and 2016. The tumour extension and node invasion was determined by imaging or histologically after upfront lymph node dissection. Clinical, biological, pathological and patient follow-up data were identified. Kaplan–Meier survival curves were compared by log rank test. Factors associated with the response to induction chemotherapy, operability of patients and survival were determined by multivariable logistic regression. Results: Among 70 patients included in the analysis, 51 (73%) showed response to induction chemotherapy. Progression-free and overall survival were improved in responder patients compared with non-responders ( P <0.0001 and P =0.025, respectively) and for patients who underwent surgery compared with non-operated patients (both P <0.001). On multivariable analysis, poor response was associated with chemotherapy other than methotrexate, vinblastine, doxorubicin and cisplatin ( P =0.016), operability with late response ( P =0.0024) and overall survival with surgery after induction chemotherapy ( P =0.0014). Conclusions: Surgery after induction chemotherapy with methotrexate, vinblastine, doxorubicin and cisplatin may improve prognosis with locally advanced or lymph node metastatic bladder cancer. Level of evidence: 4